2022
DOI: 10.3390/microorganisms10071394
|View full text |Cite
|
Sign up to set email alerts
|

“Unity and Struggle of Opposites” as a Basis for the Functioning of Synthetic Bacterial Immobilized Consortium That Continuously Degrades Organophosphorus Pesticides

Abstract: This work was aimed at the development of an immobilized artificial consortium (IMAC) based on microorganisms belonging to the Gram-positive and Gram-negative bacterial cells capable of jointly carrying out the rapid and effective degradation of different organophosphorus pesticides (OPPs): paraoxon, parathion, methyl parathion, diazinon, chlorpyrifos, malathion, dimethoate, and demeton-S-methyl. A cryogel of poly(vinyl alcohol) was applied as a carrier for the IMAC. After a selection was made between several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Fundamentally, an effective approach to the creation of consortia for the destruction of xenobiotics is a directed combination of cultures based on the preliminary selection of active PCPs destructors and an understanding of the possible interaction between them [ 80 , 100 , 101 , 102 ].…”
Section: Microbial Consortia For Biodegradation Of Pcpsmentioning
confidence: 99%
“…Fundamentally, an effective approach to the creation of consortia for the destruction of xenobiotics is a directed combination of cultures based on the preliminary selection of active PCPs destructors and an understanding of the possible interaction between them [ 80 , 100 , 101 , 102 ].…”
Section: Microbial Consortia For Biodegradation Of Pcpsmentioning
confidence: 99%
“…For example, Pseudomonas and Rhodococcus genera cells are widely represented in anaerobic consortia, which, as it turned out, have the genetic potential to synthesize enzymes that catalyze the destruction of ZEN ( Figure 3 ). At the same time, there is a positive experience of creating effective anaerobic consortia based on these Gram-positive and Gram-negative cells of the genus Rhodococcus and the genus Pseudomonas , respectively, which enhances the effect of each other, and their use is successful as a part of artificial consortia in combination with anaerobic sludge [ 110 , 111 ].…”
Section: Expected Potential In Development Of Anaerobic Biocatalysts ...mentioning
confidence: 99%
“…When combining cells into consortia, individual characteristics of cultures and the possibilities of their combination are usually taken into account. It has been shown that it is expedient to stabilize such artificial consortia by immobilization into chemically stable, non-toxic carrier matrices [69,73].…”
Section: Purification Processesmentioning
confidence: 99%